Preclinical Detection of Non-catheter Related Late-onset Sepsis in Preterm Infants by Fecal Volatile Compounds Analysis: A Prospective, Multi-center Cohort Study. Issue 4 (April 2020) - Berkhout, Daniel J.C.; Niemarkt, Hendrik J.; Andriessen, Peter; Vijlbrief, Daniel C.; Bomers, Marije K.; Cossey, Veerle; Hulzebos, Christian V.; van Kaam, Anton H.; Kramer, Boris W.; van Lingen, Richard A.; Wicaksono, Alfian N.; Covington, James A.; et al.
Abstract : Background: Late onset sepsis (LOS) in preterm infants is preceded by fecal volatile organic compound (VOC) alterations, suggesting an etiologic role of gut microbiota in LOS rather than being primarily caused by central venous catheters (CVC). To increase our knowledge about the involvement of the gut microbiota in LOS, we analyzed fecal samples from septic infants without a CVC. Methods: In this prospective multicenter study, fecal samples were collected daily from all infants born at ⩽30 weeks gestation. Fecal VOC profiles up to 3 days prior to sepsis onset from infants with non-catheter–related LOS were compared with profiles from non-septic controls by means of High-Field Asymmetric Waveform Ion Mobility Spectrometry. Results: In total, 104 fecal samples were analyzed. Fecal VOC profiles allowed for discrimination between non-catheter–related LOS cases (n = 24) and matched controls (n = 25). Discriminative accuracy increased after focusing on center of origin (area under the curve, sensitivity, specificity; 0.95, 100%, 83%) and after focusing on LOS cases caused by Staphylococcus epidermidis (0.95, 100%, 78%), the most cultured pathogen (n = 11). Conclusions: Fecal VOC profiles of preterm LOS infants without a CVC differed from matched controls underlining the increasing notion that aberrations in gut microbiota composition and activity may play a role in LOS etiology. Abstract : Supplemental Digital Content is available in the text.